Review of Dynamic Voltage Restorer Application for Compensation of Voltage Harmonics in Power Systems - Mahmoud Zadehbagheri; Rahim Ildarabadi; Majid Baghaei Nejad; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Power distribution networks are considered the main link between power industry and consumers and they are exposed to public judgment and evaluation more than any other section. Thus, it is essential to study power quality in distribution section. On the other hand, power distribution networks have always been exposed to traditional factors such as  voltage sag, voltage swell, harmonics and capacitor switching which destruct sinusoidal waveforms and decrease power quality as well as network reliability. One of the methods by which power quality problems might be addressed is to apply power electronic devices in the form of custom power devices. One of such devices is Dynamic Voltage Restorer (DVR) which is connected in series to distribution networks. At the same time, through injection of voltage to the network it is able to control voltage amplitude and phase. It is  adopted lend to compensate for voltage sags through injecting series and synchronous three phase voltage. This paper reviews on the application of DVR for Voltage Compensation in recent years and gives sets of information for each control of the DVR in distribution networks.